(3NdGUI GdCbhGd aj eYQaI GMhGd GdQLGds - (3GdMdj, CHh efUhQ, GHf GdeWgQ, LeGd GdOjf, GdMSf Hf jhSa Hf Ydj GHf GdeWgQ, J (B726(3g`s
(3ChdgG (B:s
(3ChdgG(B: (3GdaUd GdChd(B: (3aj GdgeRI, hajg KdGKI YTQ HGHG, GdHGH GdChd(B: (3EHQGgje KeGfjI hYTQhf QLdG, EHQGgje Hf kfb, HVe Gdfhfs
(3BNQgG (B:s
(3BNQgG(B: (3hcPdc cJGH NGdO Hf YHO Gddg Hf SOjQ hcGf jbhd hVY gPg GdCUhd eMeO Hf ehSi GdgePGfj, bGd GdTjN GdWhSjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B2: 227s
(3GdPQjYI, L (B7: 153s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJGQjNs